(untitled) (Research, Society and Development, 2022)
With technological advances, it is possible to use restorative materials to manufacture composite resin veneers with a low cost, minimal wear, capable of allowing an immediate aesthetic result, in which the patient achieves the necessary aesthetics and function in a single session. The objective was to present a literature review about the indications for use and longevity of direct and indirect composite resin veneers. For this, a narrative literature review was carried out, conducted through platforms of research sites. The database was searched on Google academic, SciELO and Capes journals. Including course conclusion works, dissertations, theses and articles published between the years 2001 and 2022. Direct composite resin veneers have various indications from correcting changes in color, shape, darkened or stained teeth, amelogenesis imperfecta, microdontia, alterations of position, reduction, and structural losses due to pathological wear, among others. Indirect veneers stand out as a prosthetic alternative to promote changes in teeth shape, position (slight corrections), correction of structural defects, color modification, occlusal rehabilitation, among other indications. Through correct restorative planning it is possible to achieve predictability and longevity, planning, execution, finishing and polishing factors are essential so that there are no disorders that compromise the durability of the veneers.